2018
DOI: 10.1080/00224545.2018.1466776
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision, leader-member exchange, and moral disengagement: A moderated-mediation model of organizational deviance

Abstract: This paper draws from social exchange theory and social cognitive theory to explore moral disengagement as a potential mediator of the relationship between abusive supervision and organizational deviance. We also explore the moderating effect of leader-member exchange (LMX) on this mediated relationship. Results indicate that employees with abusive supervisors engaged in moral disengagement strategies and subsequently in organizational deviance behaviors. Additionally, this relationship was stronger for those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 58 publications
3
80
0
2
Order By: Relevance
“…A significant number of studies have discussed the outcomes of abusive leadership on the attitudes and behavioral outcomes of employees in the work place. For instance, researchers have shown that high abusive supervision significantly increase employee's moral disengagement [27], employees stress and turnover intentions, interaction avoidance [28], and organizational dehumanization [29]. Similarly, a meta-analytic review of the consequences of abusive supervision shows that abusive supervision has negative effect on the job satisfaction, affective commitment, and organization identification [30].…”
Section: Abusive Supervision and Trust-in-supervisormentioning
confidence: 99%
“…A significant number of studies have discussed the outcomes of abusive leadership on the attitudes and behavioral outcomes of employees in the work place. For instance, researchers have shown that high abusive supervision significantly increase employee's moral disengagement [27], employees stress and turnover intentions, interaction avoidance [28], and organizational dehumanization [29]. Similarly, a meta-analytic review of the consequences of abusive supervision shows that abusive supervision has negative effect on the job satisfaction, affective commitment, and organization identification [30].…”
Section: Abusive Supervision and Trust-in-supervisormentioning
confidence: 99%
“…Abusive supervision, as a negative leadership behavior, is produced when a leader ignores the feelings of employees and deals with them with excessive words or abusive behavior [ 9 , 42 ], thus creating stressful situations for employees and forcing them to adjust their cognition and behavior in order to achieve consistency with the environment [ 48 ]. Employees cannot take actions to resist because of the gap separating them from their supervisors, thus increasing the psychological pressure on them and stoking concerns about the continuity of their work and access to important work resources—ultimately, resulting in job insecurity [ 29 ]. Previous studies have tended to focus on the impact of positive leadership behavior on job insecurity, advocating an increase in such behavior to alleviate job insecurity [ 7 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Employees become “outsiders” who are in low-quality LMX relationships with their leaders. Abusive supervisory behavior includes ridicule and neglect of employees, which may cause employees to perceive that their expectations of affective exchanges have been violated [ 29 ]. The resulting poor LMX relationships between employees and leaders are only limited to the scope of formal work [ 26 , 30 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…As stated, subordinates will pay attention to the self-serving intentions of high Machiavellian leaders engaging in UPB and tend to treat the leaders as immoral persons. Then, they will develop a moral cognitive bias that unethical behaviors are normal (Ashforth and Anand, 2003;Valle et al, 2019). In this case, high moral disengagement of subordinates appears.…”
Section: The Mediating Role Of Moral Disengagementmentioning
confidence: 99%